2022
DOI: 10.3390/cells11050760
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Organoids Maintain the Expression of Neural Stem Cell-Associated Glycoepitopes and Extracellular Matrix

Abstract: During development, the nervous system with its highly specialized cell types forms from a pool of relatively uniform stem cells. This orchestrated process requires tight regulation. The extracellular matrix (ECM) is a complex network rich in signaling molecules, and therefore, of interest in this context. Distinct carbohydrate structures, bound to ECM molecules like Tenascin C (TNC), are associated with neural stem/progenitor cells. We have analyzed the expression patterns of the LewisX (LeX) trisaccharide mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 69 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…4 ). Moreover, the co-localization of nestin and intermediate progenitor cell marker, (T-box brain protein 2) TBR2 indicate that the cerebral organoids possessed well-defined progenitor zone organization and neural identity 58 for all dynamic systems at day 120 but mostly in µ-platform and RCCS (Fig. 4a–c , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 97%
“…4 ). Moreover, the co-localization of nestin and intermediate progenitor cell marker, (T-box brain protein 2) TBR2 indicate that the cerebral organoids possessed well-defined progenitor zone organization and neural identity 58 for all dynamic systems at day 120 but mostly in µ-platform and RCCS (Fig. 4a–c , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Contrary to its function in these processes, its role in NPSCs is less known. Several studies have reported that CSPG is required for maintaining a stemness state in NPSCs in the SVZ, and have suggested that this activity is mediated by interaction with FGF-2 to promote cell proliferation (Bian et al, 2011;Roll et al, 2022;Sirko et al, 2010a). In spinal cord NSPCs, such FGF-2 activity was recently found to depend on the sulfation patterns of the CSPG-GAG chains that operate as docking sites for specific proteins (Schaberg et al, 2021).…”
Section: The Role Of Csps In the Hbsmentioning
confidence: 99%
“…b) This schematic illustrates the temporal changes in the neural stem cell-associated glycoepitopes and ECM molecules present in human cerebral organoids. Reproduced with permission [81]. Copyright 2022, MDPI.…”
mentioning
confidence: 99%
“…e) Proliferation in early cerebral organoids. Reproduced with permission [81]. Copyright 2022, MDPI.…”
mentioning
confidence: 99%